PRELIMINARY ASSESSMENT OF THE EFFECT OF BOTTOM WARP ON THE DYNAMICS OF PLANING HULLS USING OPENFOAM - Paredes R. J.; Plaza D.; Marin-Lopez J. R.; Begovic E.; Datla R. (Volume 7: CFD & FSI, 2023)
The prediction of the dynamics of High-Speed Craft (HSC) with prismatic hulls is commonly performed by designers using semi-empirical formulations based on Savitsky’s classic method. However, the accuracy of this prediction decreases with the presence of warp, when the deadrise of the hull change along its length, which is typical for small passenger ferries, even when considering the effective deadrise and trim angle concept proposed by Savitsky in 2012. The present work assessed the dynamics of three planing warped hulls and one prismatic monohull developed by the University of Naples, using a morphing grid approach implemented in OpenFOAM to capture the motion of the vessel. Numerical results on resistance, wetted area, dynamic trim angle, wall shear stress, and pressure distribution were compared with the method proposed by Savitsky, and previously published results where possible. Results suggested that it is possible to improve Savitsky prediction by changing the location where the equivalent deadrise angle is evaluated. This single modification will allow to extend the application of Savitsky method for a wider range of warp rates.